The Living Law in Judicial Decisions: Formulation and Implications of the National Criminal Code - Rian Sulistio; I Nyoman Nurjaya; Abdul Madjid (Jurnal Dinamika Hukum, 2025)
A good law is a law that is in accordance with the law that lives in the community (living law) and in accordance with the reflection of the values prevailing in the community. In its development, living law has been accommodated in Article 2 paragraph (1) of the National Criminal Code. This research analyzes the formulation of living law provisions in the community in the National Criminal Code and its implications for Judges in making legal considerations in their decisions. This research uses normative juridical research method with statutory, historical, conceptual, analytical, and case approaches. The results showed that the formulation of Laws Living in Society in the National Criminal Code contained 15 provisions with five variations of terms such as “laws living in society”, “norms of decency”, “values of law and justice”, “local customary obligations”, and “fulfillment of customary obligations”, then the implications of laws living in society in the National Criminal Code have consequences for Judges can be a reference for adjudicating cases involving customary law and additional legal considerations. Although there are no Government Regulations and Regional Regulations regarding laws that live in the community, Judges are still obliged to explore legal values and a sense of justice that live in the community.